Stereotactic Radiosurgery for Perioptic Meningiomas: An International, Multicenter Study. (18th December 2021) - Bunevicius, Adomas; Anand, Rithika Kormath; Suleiman, Mohanad; Nabeel, Ahmed M; Reda, Wael A; Tawadros, Sameh R; Abdelkarim, Khaled; El-Shehaby, Amr M N; Emad, Reem M; Chytka, Tomas; Liscak, Roman; Sheehan, Kimball; et al.
Graphical Abstract: